Can there be a Progressive Nostalgia? Layering Time in Pride’s Retro-Heritage - Louis Bayman (Open Library of Humanities, 2019)
Pride is notable for its dynamic treatment of time, which is key both to its appeal as a film and to its presentation of the processes of political change. By combining nostalgia, retro, and heritage, Pride manifests an artistic practice I refer to as temporal layering, which draws attention to how any single moment implies potential relationships with numerous interacting others. I use this notion to understand both the role that the 1984–5 miners’ strike assumes in cultural revisions of the 1980s, and the kind of cinematic past that Pride presents. This past can be understood as a development in the heritage genre appropriate to reimagining modern British history, especially that of the 1980s,  that could be called retro-heritage. By paying attention to the varied temporal layers thus present in Pride, a new perspective is offered on how nostalgia’s presumed conservatism sits alongside the ‘left-wing melancholy’ (Traverso, 2017) that has dominated in the era of defeats since the 1980s. My ultimate aim is to ask what potential nostalgia may have when envisaging a different future.1